Penerapan Strategi Inkuiri Untuk Meningkatkan Kemampuan Saintifik Siswa Dalam Pembelajaran Biologi SMA: (Application of Inquiry Strategy to Improve Students' Scientific Ability in High School Biology Learning) - Nurlailatus Safitri; Putri Prisilia Saragih; Thahara Sumayya Zukarnain; Pinkan Deviana Khairunnisa; Indayana Febriani Tanjung (BIODIK, 2022)
The purpose of this research is to improve students' scientific ability, by applying inquiry learning strategies in biology learning. This research is in the form of classroom action research with qualitative data analysis. Based on observational data on students' scientific abilities, it is known that in the first cycle for aspects A (asking) and B (observing) all students obtained the "very good" criteria and the "good" criteria with a 100% percentage. Then for aspects of C (gathering information), D (processing information) and E (communication) the number of students who got the "not good" criteria showed a fairly high percentage, namely 86.7% (26 people), 90% ( 27 people) and 73% (22 people). In cycle II there was an increase in every scientific aspect of students, especially in the three aspects that were lacking in cycle I. The number of students who had "good" criteria in the scientific aspects of C (gathering information) and E (communication) amounted to 30 people with a percentage of 100%. As for the scientific aspect D (processing information), 29 students were categorized as "good" or with a percentage of 96.7%.It can be concluded that the increase in students' scientific ability is due to the application of inquiry learning strategies. Key words: Inquiry, Biology, Ability, Scientific Â  ABSTRAK Tujuan penelitian adalah untuk meningkatkan kemampuan saintifik siswa, dengan menerapkan strategi pembelajaran inkuiri dalam pembelajaran biologi. Penelitian ini berbentuk penelitian tindakan kelas dengan analisis datasecera kualitatif. Berdasarkan data hasil observasi terhadap kemampuan saintifik siswa, diketahui bahwa pada siklus I untuk aspek A (menanya) dan B (mengamati) seluruh siswa memperoleh kriteria â€œsangat baikâ€ dan kriteria â€œbaik dengan persentasi 100%. Kemudian untuk aspek C (mengumpulkan informasi), D (mengolah informasi) dan E (komunikasi) jumlah siswa yang mendapat kriteria â€œkurang baikâ€ menunjukkan persentase yang cukup tinggi yaitu masing-masing sebesar 86,7% (26 orang), 90% (27 orang) dan 73% (22 orang). Pada siklus II terjadi peningkatan terhadap setiap aspek saintifik siswa, terutama pada ketiga aspek yang kurang pada siklus I. Jumlah siswa yang berkriteria â€œbaikâ€ pada aspek saintifik C (mengumpulkan informasi) dan E (komunikasi) berjumlah 30 orang dengan persentase sebesar 100%. Sedangkan untuk aspek saintifik D (mengolah informasi), sebanyak 29 orang siswa masuk kategori kriteria â€œbaikâ€ atau dengan persentasi sebesar 96,7%. Dapat disimpulkan meningkatnya kemampuan saintifik siswa dikarenakan penerapan strategi pembelajara inkuiri. Kata kunci: Inkuiri, Biologi, Kemampuan, Saintifik Â